2022
DOI: 10.18471/rbe.v36.48621
|View full text |Cite
|
Sign up to set email alerts
|

Ambientes De Trabalho De Enfermagem Durante a Covid-19: Contribuições Para Desenvolver Uma Ferramenta Tecnológica

Abstract: Objetivo: avaliar o impacto da COVID-19 nos ambientes de trabalho de enfermagem e desenvolver uma ferramenta tecnológica para avaliar sistematicamente a qualificação desses contextos. Método: pesquisa de método misto realizada em seis hospitais portugueses, com participação de 442 enfermeiros. Utilizou-se um questionário com caracterização sociodemográfica e profissional, a Scale for the Environments Evaluation of Professional Nursing Practice e questões abertas. Resultados: a COVID-19 teve impacto negativo no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…During institutionalization, the Nursing team is responsible for 95% of the care provided to patients in health organizations. Thus, knowing the characteristics found in the work environment, such as the relationship with the medical team, the autonomy and management that nurses have in patient care, should emerge as a priority for managers who are concerned with the excellence of institutional results 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During institutionalization, the Nursing team is responsible for 95% of the care provided to patients in health organizations. Thus, knowing the characteristics found in the work environment, such as the relationship with the medical team, the autonomy and management that nurses have in patient care, should emerge as a priority for managers who are concerned with the excellence of institutional results 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted to assess the presence of characteristics that favor the professional Nursing practice 2,12,13,14,15 . A review of the national and international literature 16 showed that the most widely used instruments for such purpose are the Nursing Work Index -Revised (NWI-R) and the Practice Environment Scale (PES), already validated in Brazil.…”
Section: Introductionmentioning
confidence: 99%